2012
DOI: 10.2522/ptj.20110378
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Feedback Frequency and Task Difficulty in Children's Motor Skill Learning

Abstract: Structuring practice conditions for children should take into account task complexity and feedback frequency in determining the cognitive challenge necessary for optimal skill learning. More generally, the findings suggest that practitioners teaching motor skills should design practice conditions in accordance with the cognitive processing capacity of the learner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 17 publications
5
66
0
2
Order By: Relevance
“…Both groups of children showed marked improvements in accuracy and consistency during the 200 acquisition trials with their performance preserved the following day during retention tests. Our findings documenting motor learning changes with augmented feedback are consistent with other studies of children with typical development and children with CP . Although other studies have reported positive effects of feedback manipulations (mirror visual feedback, knowledge of performance, etc.)…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both groups of children showed marked improvements in accuracy and consistency during the 200 acquisition trials with their performance preserved the following day during retention tests. Our findings documenting motor learning changes with augmented feedback are consistent with other studies of children with typical development and children with CP . Although other studies have reported positive effects of feedback manipulations (mirror visual feedback, knowledge of performance, etc.)…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between our findings and these researchers may be the complexity of the task learned since children in our study practised a rapid spatially and temporally constrained task. In another study, children with typical development practised two simple and complex throwing tasks. During the simple throwing task, children benefited the most from 33% feedback; however, children who received 100% feedback as they learned the complex throwing task performed with less error in a delayed retention test and with greater accuracy in a transfer test to a new motor task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented feedback can enhance learning but it has also been found that too much can hinder learning. 61 Our patients naturally become dependent on feedback when it is provided to them. Feedback that is more frequent encourages passive rather than active participation and can reduce the patient's ability to perform those skills.…”
Section: The Role Of Feedbackmentioning
confidence: 99%
“…With regard to the development of motor skills, research has found that children with impaired motor‐skill development benefited more from less‐frequent feedback as compared with children with typical motor‐skill development (Hemayattalab & Rostami, ; Sidaway, Bates, Occhiogrosso, Schlagenhaufer, & Wilkes, ). In cognitive processes, feedback frequency depends on the age of the performer; younger performers benefited from increased feedback frequency whereas older performers are able to make cognitive corrections before receiving feedback (Scruton, Webb, & Holland Fiorentino, ).…”
Section: Relevant Literaturementioning
confidence: 99%